Quantitative determination of the anticancer prodrug combretastatin A1 phosphate (OXi4503, CA1P), the active CA1 and its glucuronide metabolites in human urine and of CA1 in plasma by HPLC with mass spectrometric detection. - Stratford, MR; Folkes, L (2012)
Validated methods for the determination of CA1, the active agent derived from the prodrug CA1P, in human plasma and urine, and of CA1P and three glucuronides CA1G1, CA1G2 and CA1DG in human urine were developed using LC-MS. Plasma CA1 was extracted using solid phase extraction and validated over the range 5-1000 nM. Urine samples were analysed without extraction, and the assays validated over the range 50-2000 nM (CA1P), 25-2000 nM (CA1), 50-40,000 nM (CA1G1 and CA1G2) and 25-4000 nM (CA1DG). The mean correlation coefficient (r²) was ≥ 0.997 for all assays. The intra-day and inter-day accuracy and precision were within the generally accepted criteria for bioanalytical methods (<15%). Mean recovery of CA1 from plasma was 101%, and 97% from urine. Mean urine recovery of CA1P was 98%, CA1G1 96%, CA1G2 93% and CA1DG 93%. The method was applied to plasma and urine samples from a recently completed clinical trial of the prodrug. Peak plasma concentrations of up to 470 nM CA1 were seen. The majority of drug-related material measured in urine comprised of the two monoglucuronides; CA1 and the diglucuronide were about 10-fold lower. No CA1P was detectable in urine.